Micro, meso, macro : addressing complex systems couplings - Liljenström, Hans, 1956-; Svedin, Uno, 1943- (World Scientific, 2005)
In the domain of science concerned with systems structure and behavior, the issue of the relationship between the micro and the macro level is of key importance. This book concentrates on the interplay between these levels and has a special focus on the level "in between"--The meso level. An investigation of those links is made through a number of cases from different domains of science, including physics, chemistry, ecology, social science, economics and technology. What is evident is that there are facets regarding meso-level issues that are similar between cases, but also that the domains differ in various ways. This is particularly exemplified by the differences in perspectives from which the natural and social sciences deal with scaling issues. The various examples provided in this book mirror its overriding theme: systems complexity.